DESIGN OF BACKBONE NETWORK INFRASTRUCTURE DATA COMMUNICATIONS IN TAMBRAUW REGENCY - Jamlean, Alexander (Electro Luceat, 2015)
Figure of backbone network infrastructure plan to be one part in the development of information technology in the Tambrauw regency . Network based on wireless technology as the development of wired technology in its implementation requires accurate field by survey .The study was conducted through a survey of early stages of determining the location coordinates for the placement of a variety of network equipment that supports the development of wireless technology . The survey becomes important when there is the challenge of the Tambrauw regency topography consisting of a stretch of hills and mountains . The field survey was conducted in 7 subdistricts by using GPS ( Global Positioning System ) . The survey was conducted by considering the visual line of sight with the help of the local community through the interview method .The problem essentially , how the placement of the tower site selection for the interconnectedness between districts with heavy field surveys , so that topographic analysis using the Global Mapper software also Google Eart 11:02 6.0.0.1735 ( beta ) is very helpful , and eventually earned a 20 point location coordinates as a candidate placement equipment with a single hop network without repeaters . Fresnel zone radius is on the radar on the interconnectedness between subdistricts in Tambrauw regency , through partial mesh topology provides benefits interconnectedness between subdistricts are stable because it has a backup path .Â Bibliography (2000 - 2014)Â